A REVIEW OF EPOXY-NANOCOMPOSITE PROPERTIES - Abbas , Samer Saad; Raouf , Raouf Mahmood; Al-Moameri, Harith (Journal of Engineering and Sustainable Development, 2024)
Epoxy resins have been the subject of many studies as a consequence of their extensive usage in recent years. The brittleness and low resistance to propagation and crack initiation of epoxy resins are well-recognized characteristics. Therefore, in recent years, experts have concentrated on increasing epoxy resin’s fracture resistance. Adding inorganic nanoparticles like titanium dioxide (TiO2) TiO2, silica (SiO2), carbon black, alumina (Al2O3), and others to the polymer matrix is one of the most investigated techniques in polymer science. Despite having a modest nanofiller content, the resulting nanocomposites may enhance their thermal, mechanical, rheological, electrical, and optical characteristics. These nanocomposites are an alternative to metal-based materials. They have great promise as multifunctional materials in a range of applications, including optoelectronic devices, semiconductor devices, civil engineering, automotive, and aerospace. To show potential future directions and market prospects for polymer nanocomposites reinforced with TiO2 nanoparticles, current results, and trends have been examined and highlighted. In addition, the current review surveys many studies that highlighted using nanoparticles as reinforcement, their different structure, the interface, and the geometry and structure of the resulting nano-materials reinforced resin.